Dual-curable PVB based adhesive formulations for cord/rubber composites: The influence of reactive diluents - YILDIZ, ZEHRA (ELSEVIER SCI LTD, 2017)
In this study, the effects of reactive diluent type on the adhesion strength of cord/rubber surfaces were investigated. For this purpose, a urethane acrylate oligomer was synthesized by the reaction of 2,4-toluene diisocyanate (TDI), 2-hydroxyethyl methacrylate (HEMA) and polyvinyl butyral (PVB) in the presence of di-n-butyltin dilaurate (T12) as catalyst. The structure of the oligomer was characterized by nuclear magnetic resonance (NMR) spectroscopy. Then the oligomer was included in adhesive formulations together with trimethylolpropane trimethacrylate (TMPTMA) and tricyclodecane dimethanol diacrylate (TCDDA) as reactive diluents and thermal and photo initiator respectively. Polyester/polyamide cord fabrics were dipped into the adhesive solution and cured by UV-light. Then coated fabrics were characterized by Fourier transform infrared (FTIR) spectroscopy, differential scanning calorimetry (DSC) and thermal gravimetric analysis (TGA). Contact angle measurement was employed to investigate the wettability properties of the coated fabrics. Thermal curing between the coated fabric and rubber was performed under heat and pressure. The adhesion strength between the cord/rubber surfaces was determined by T-peel test. The highest adhesion strength of 100.4 N/cm with the lowest contact angle value of 70.2 were obtained in the sample containing TCDDA as reactive diluent, due to a higher functionality resulting in a greater crosslinking density.
Keywords: UV-curing; Adhesion; Polyvinyl butyral; Reactive diluent; Cord fabric; POLYETHYLENE TEREPHTHALATE; POLYURETHANE ACRYLATE; RUBBER; POLYMERIZATION; DERIVATIVES; SYSTEM; FILMS; RESORCINOL; STABILITY; MONOMERS